Visiones sobre el poder (2007)
ABSTRACT: The following considerations will deal with conceptions about the power emanating from diverse theoretical and ideological guidance epistemic, as dissimilar as can be the names of Marx, Foucault, Luhmann, Max Weber and Elias Canetti. They agree the first in a structural assessment of power beyond their differences in the approach of the same.